IoT-Based Architecture Using Node-RED and MQTT for Environmental Monitoring in Agricultural Settings - Romero Molano, Cesar Augusto (2025)
The Internet of Things (IoT) enables the interconnection of sensors and actuators to provide scalable, effective, and low-cost solutions capable of collecting, transmitting, and processing real-time information. In the agricultural sector, the lack of integrated systems for environmental monitoring limits the efficient management of resources and timely responses to climatic variations. In this context, the objective of this work was to design and implement an IoT architecture for real-time monitoring of ambient temperature and humidity, using DigitalOcean as the cloud server, Node-RED as the integration environment, and the MQTT protocol for data transmission. An ESP32 microcontroller connected to a DHT11 sensor was employed, managed by the Mosquitto broker, with data storage in MySQL and visualization through a dashboard developed in Node-RED. The results demonstrated stable communication, with an average transmission time of two seconds and no data loss during testing. The proposed architecture proved to be an efficient, reproducible, and low-cost solution, suitable for academic and agricultural environments requiring continuous and reliable environmental supervision.